If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4q + 4q + -16 = -8(-4q + 14) Reorder the terms: -16 + 4q + 4q = -8(-4q + 14) Combine like terms: 4q + 4q = 8q -16 + 8q = -8(-4q + 14) Reorder the terms: -16 + 8q = -8(14 + -4q) -16 + 8q = (14 * -8 + -4q * -8) -16 + 8q = (-112 + 32q) Solving -16 + 8q = -112 + 32q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-32q' to each side of the equation. -16 + 8q + -32q = -112 + 32q + -32q Combine like terms: 8q + -32q = -24q -16 + -24q = -112 + 32q + -32q Combine like terms: 32q + -32q = 0 -16 + -24q = -112 + 0 -16 + -24q = -112 Add '16' to each side of the equation. -16 + 16 + -24q = -112 + 16 Combine like terms: -16 + 16 = 0 0 + -24q = -112 + 16 -24q = -112 + 16 Combine like terms: -112 + 16 = -96 -24q = -96 Divide each side by '-24'. q = 4 Simplifying q = 4
| 12-1*0-4/2= | | 6x-10=-7x+14 | | 3a+12-6a=19 | | (3y^2+4xy)dx+(2xy+x^2)dy=0 | | (-9r^3+2r+1)-(-5r^2+r+8)=0 | | 2(16.5x)+2(16.5)=50 | | 7-19j+11j=2(-13j+13)+19j | | V=w*l*h | | 27-2x=16+9x | | .0625x=4.5 | | 2y-8y+3=9 | | -3(-10c+5)=c-2(-16c-3) | | 2x-7=11fory | | 3(x-8)=3x | | 18y=3(9y+3) | | 6k-(7-6k)=-89 | | x-(-26)=6 | | 5x+8y+6=0 | | 2(14.75x)+2(14.75)=50 | | 6(8n+5)=-3(-18n-6) | | 12m+9=2m-11 | | 3(p+3)=-7p+39 | | 2(14.5x)+2(14.5)=50 | | 3x-3=-204 | | 11h-13=4(9h+17)+19 | | -8-x=x-3x | | 4(2+w)=35 | | -6+17=4-8+y | | 6-7x=7x-10x+4 | | 2(15.75x)+2(15.75)=50 | | R=6(a+b) | | -99.533753=3.839(4.7a-0.5) |